Formation. Characterization and Stability Analysis of Cracks and Vertical Leg Fissures in Mole Drainage: Results of Laboratory Simulation - Mishra, A.K.; Sarkar, T.K.; Bhattacharya, A.K. (Journal of Soil and Water Conservation, 2022)
A laboratory simulation study of Mole Drain characteristics on heavy textured soils of I.A.R.I. farm (clay content 20.3-32.3%) was carried out to analyze the process and mechanism of formation and characteristics of surface cracks and vertical leg fissures; during mole channel laying operation and stability of channels before, during and after operation under a variety of initial and final soil moisture and soil bulk density combinations (at the time of moling). The present paper highlights the results of quantitative as well as qualitative observations on above parameters. The study concludes that to obtain a relatively stable mole channel and good formation of cracks and leg fissures not only the clay content of the soil but the initial soil moisture and bulk density are directly responsible but also affect the channel stability. In order to obtain a relatively more stable channel that can retain its shape for effective operative life of 5-8 years these parameters need to be maintained before the operation of mole channel lying